Pengaruh organizational reward dan procedural justice terhadap perceived organizational support serta job embeddedness - Isma, Said Muhammad; Mintarti, Sri; Tricahyadinata, Irsan (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2020)
The purpose of this study is to examine the role of perceived organizational support as a mediator between organizational rewards and procedural justice on job embeddedness. Respondents study were 214 people who were employees of the Inche Abdoel Moeis Samarinda Regional Hospital (RSUD). Tthe Partial Least Square (PLS) approach for data analysis. The result of the study found that organizational rewards has significant effect on job embeddedness. Organizational reward has significant effect on perceive organizational support of employees. In other words, the organizational rewards influence employees' confidence in the organization regarding the appreciation of their contribution and care for their well-being. Additionally, the procedural justice has significant effect on embeddedness job of employees. The higher the procedural justice, it will affect the perceive organizational support. In other words, procedural justice influences employees' confidence in the organization regarding respect for their contribution and care for their welfare. This means that the higher the perceive organizational support, the higher of the job embeddedness. Finally, implications will be further discussed.